2011
DOI: 10.1007/s11060-011-0685-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for involvement of ROCK signaling in bradykinin-induced increase in murine blood–tumor barrier permeability

Abstract: We have previously shown that activation of RhoA by bradykinin (BK) is associated with cytoskeleton rearrangement, tight junction (TJ) protein disassembly, and an increase in blood-tumor barrier (BTB) permeability in rat brain microvascular endothelial cells (RBMECs). Subsequently, we investigated whether Rho-kinases (ROCKs), a family of downstream effectors of activated RhoA known to stimulate F-actin rearrangement, play a key role in the above-mentioned processes in RBMECs. Our study uses primary RBMECs as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
(86 reference statements)
3
16
0
Order By: Relevance
“…The reorganization of the actin cytoskeleton induced by neutrophils in ECs and the capacity of BAPTA/fasudil treatment to prevent gap formation suggest a role of actomyosin contraction in the EC response upon neutrophil degranulation and activation of BK B 2 receptors. The mechanisms downstream of BK B 2 receptor signaling eventually leading to openings of endothelial cell junctions have been investigated and suggested to involve VE-cadherin disassembly (36) and increased actomyosin interaction (37). Although it was beyond the scope of our study to define the involvement of these cellular responses in further detail, our data do not exclude a role of VE-cadherin disassembly in parallel with actin reorganization.…”
Section: Discussionmentioning
confidence: 71%
“…The reorganization of the actin cytoskeleton induced by neutrophils in ECs and the capacity of BAPTA/fasudil treatment to prevent gap formation suggest a role of actomyosin contraction in the EC response upon neutrophil degranulation and activation of BK B 2 receptors. The mechanisms downstream of BK B 2 receptor signaling eventually leading to openings of endothelial cell junctions have been investigated and suggested to involve VE-cadherin disassembly (36) and increased actomyosin interaction (37). Although it was beyond the scope of our study to define the involvement of these cellular responses in further detail, our data do not exclude a role of VE-cadherin disassembly in parallel with actin reorganization.…”
Section: Discussionmentioning
confidence: 71%
“…F-actin is a major contractile protein of the cytoskeleton, and its reorganization and redistribution in epithelial cells may impair intestinal barrier function by altering the structure of intestinal TJ-associated proteins. Cytoskeletal actin links to the C-terminal region of TJ protein ZO-1 and influences its expression and structure [33]. Cytoplasmic protein ZO-1 could further bind to the C-terminal binding sequence of the transmembrane protein claudin-1 and participate in maintaining the stability of epithelial TJ [6, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…First, blockade of ACE increases the bradykinin concentration, and it is known that the kinin system influences carcinogenesis by stimulating the growth, survival, and migration of cancer cells by altering the permeability of the blood tumor barrier and through the release of proinflammatory cytokines [35][36][37][38]. In addition, Fernandes et al [39], using a murine model of Ehrlich tumor, found that bradykinin antagonists may inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%